Tuti, Poe, Pontu ja minu teised lemmikud - Ülo Siimets (Mäetagused, 2006)
Everyone has encounters with animals, pets, birds or fish. These are personal encounters that belong to him, his acquaintances, friends, children. Usually having a pet has a sad ending since the lifespan of most pets is markedly shorter than that of people. In the present work the author reminiscent on the cats, dogs, duck, fish and other animals from his childhood.